Innovative perspective of teacher management in the andragological field. (Revista Electrónica REDINE, 2018)
This article referring to university teacher as innovator, using for this andragogical learning processes, representing a change in the traditional academic culture, thus the university teacher must be aware of the changes that occur, these changes inserted in universities complexity of interactions, conflicts and uncertainties, which implies a reform in the thinking of teachers, for that Drucker (2006) made an assumption that facilitates this process that also contributes to the continuous and systematic improvement in the practice of educational managers: leave yesterday, is not stay in the past, but learn from it and have a realistic view of the situations that can contribute to the improvement to use it as an opportunity.
Keywords: innovation; andragogy; change